Expanding the antiprotozoal activity and the mechanism of action of n-butyl and iso-butyl ester of quinoxaline-1,4-di- N -oxide derivatives against Giardia lamblia, Trichomonas vaginalis, and Entamoeba histolytica: An in vitro and in silico approach - González González, Alonzo (2024)
In this study, n-butyl and iso-butyl quinoxaline-7-carboxylate-1,4-di-N-oxide derivatives were evaluated in vitro against Giardia lamblia (G. lamblia), Trichomonas vaginalis (T. vaginalis), and Entamoeba histolytica (E. histolytica). The potential mechanism of action determination was approached by in silico analysis on G. lamblia and T. vaginalis triosephosphate isomerase (GlTIM and TvTIM, respectively), and on E. histolytica thioredoxin reductase (EhTrxR). Enzyme inactivation assays were performed on recombinant GlTIM and EhTrxR. Compound T-167 showed the best giardicidal activity (IC50 = 25.53 nM) and the highest inactivation efficiency against GlTIM without significantly perturbing its human homolog. Compounds T-142 and T-143 showed the best amoebicidal (IC50 = 9.20 nM) and trichomonacidal (IC50 = 45.20 nM) activity, respectively. Additionally, T-143 had a high activity as giardicial (IC50 = 29.13 nM) and amoebicidal (IC50 = 15.14 nM), proposing it as a broad-spectrum antiparasitic agent. Compounds T-145, and T-161 were the best EhTrxR inhibitors with IC50 of 16 µM, and 18 µM, respectively.